Asbestos accelerates disease onset in a genetic model of malignant pleural mesothelioma - Pooyeh Farahmand; Katarina Gyuraszova; Claire Rooney; Claire Rooney; Ximena L. Raffo-Iraolagoitia; Geeshath Jayasekera; Ann Hedley; Emma Johnson; Tatyana Chernova; Gaurav Malviya; Holly Hall; Tiziana Monteverde; et al. (Frontiers in Toxicology, 2023)
Hypothesis: Asbestos-driven inflammation contributes to malignant pleural mesothelioma beyond the acquisition of rate-limiting mutations.Methods: Genetically modified conditional allelic mice that were previously shown to develop mesothelioma in the absence of exposure to asbestos were induced with lentiviral vector expressing Cre recombinase with and without intrapleural injection of amosite asbestos and monitored until symptoms required euthanasia. Resulting tumours were examined histologically and by immunohistochemistry for expression of lineage markers and immune cell infiltration.Results: Injection of asbestos dramatically accelerated disease onset and end-stage tumour burden. Tumours developed in the presence of asbestos showed increased macrophage infiltration. Pharmacological suppression of macrophages in mice with established tumours failed to extend survival or to enhance response to chemotherapy.Conclusion: Asbestos-driven inflammation contributes to the severity of mesothelioma beyond the acquisition of rate-limiting mutations, however, targeted suppression of macrophages in established epithelioid mesothelioma showed no therapeutic benefit.